PENGEMBANGAN DESAIN PEMBELAJARAN TOPIK POLA BILANGAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) DI KELAS VIII SMP/MTs - FITRI DIANA (Jurnal Edukasi dan Penelitian Matematika, 2018)
The result of preliminary studies suggest that students’ mathematical reasoning abilities on topic number pattern was low. This is due to the teaching of teachersthat are too focused on textbooks. While the presentation of material number pattern on textbook has not been optimal and less to contribute to the development of student learning, especially on students’ mathematical reasoning abilities. Therefore, in designing instructional design of number pattern topic based on realistic mathematics education is implemented in student worksheet. This research that was Gravemeijer & Cobb development model, which  consisted of three phases, there were the preparing experiment, design experiment and retrospective experiment. The subject were 8th grade students of 1 Padang Junior High School. Data analysis techniques used are descriptive statistics and descriptive techniques, which describe the validity, practicality and effectiveness of instructional design through student worksheet based on RME. Instrument data collection used : final test, observation sheets, interview sheets and questionnaires. The result of the research shows that the instructional design of number pattern topic with RME approach through student worksheet have been valid, practical and effective. It is to be valid because it has fulfilled the characteristics of the validity of both content and construct contents. It is said to be practical because the product is easy to use and understand, the specified time allocation is very efficient, very interesting and contributes to the number pattern learning. Furthermore it is said to be effective because the use of this design has a potential impact on students’ reasoning abilities on the topic of number pattern.Keywords:Instructional Design, Number Pattern, RME, Learning Trajectory, Design Research